KINERJA PEMERINTAH DESA DALAM PENYELENGGARAAN PEMBANGUNAN NON FISIK DI DESA TOLOTOYON KECAMATAN PINOLOSIAN KABUPATEN BOLAANG MONGONDOW SELATAN - MOKOAGOW, MUSLIH; LENGKONG, FLORENCE; LONDA, VERY (Sam Ratulangi University, 2020)
The purpose of this study was to determine the performance of the village government in the implementation ofnon-physical development in Tolotoyon Village, Pinolosian District, Bolaang Mongondow Selatan District. Thisstudy uses a qualitative method. There were 10 informants in this study consisting of the Village Head (1 person),Village Secretary (1 person), Head of General Affairs and Village Planning (1 person), Head of Welfare andServices Section (1 person), BPD (1 person), and the community (5 people). Based on the results of researchconducted by the author, that : in general the performance of village governments in the implementation of nonphysicaldevelopment based on (1) Productivity or referring to the work of public organizations is good startingfrom the planning process, program preparation, and implementation of development in the non even thoughphysical results have not yet reached optimal results, where there are still non-physical development programsthat have not yet been realized. (2) Responsiveness The ability to recognize the needs of the community is goodwhere the village government is always open in terms of receiving proposals and what is the complaint from thecommunity. Seen from a number of proposals from the community that are included in the non-physicaldevelopment plan and the response from the village government itself is very accepting and supporting what thecommunity proposes. (3) Accountability shows the size of policies and activities of the public sector that can beaccountable to the public. The process of village government accountability in the implementation of nonphysicaldevelopment has shown a positive thing by making a report on the realization of the development programdelivered by the leadership in this case the village head to all levels of village government, BPD, and thecommunity in joint meetings or deliberations. This accountability report is submitted in oral and written formand in the form of documentation of programs that have been realized or have been carried out.Keywords: Performance, Village Government, Non-Physical Development